Export behaviour of Pakistani firms: An evaluation of interviews - G. B. S. Mujahid (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1975)
One of the remarkable features of Pakistan's economic performance since the mid-Fifties has been its success in achieving high rates of growth of manufacturing output and manufactured exports. During the political crisis of 1969-1971, which led to the formation of an independent Bangladesh, the advocates of its' independence attributed this success largely to Pakistan's union with Bangladesh. However, as shown by an analysis of published aggregate data, within a short period of four years after the separation of Bangladesh, Pakistan was once again able to achieve high rates of increase in both manufacturing output and manufactured exports. The limitations of statistics published by Governments are well-known. Not only are the available statistics highly aggregated, but also these statistics often fail to provide answers to relevant questions. Moreover, qualitative information on aspects such as factors affecting export growth and suggestions for policies is not available. It was to supplement information on manufactured exports and to obtain first-hand knowledge at the firm level of problems facing Pakistan's exporters both as a result of the separation of Bangladesh and otherwise, that a sample survey of manufacturing-cum-exporting firms was conducted during the period, November 1974 - March 1975. This study reports and analyses the findings of the Survey.
Keywords: 330